OS4.1 MEVITEM: A European, randomized, open-label, Phase I/II study of vismodegib in combination with temozolomide versus temozolomide alone in adult patients with recurrent or refractory medulloblastoma presenting an activation of the Sonic Hedgehog (SHH) pathway. (6th September 2019) - Frappaz, D; Barritault, M; Montané, L; Laigle-Donadey, F; Chinot, O; Le Rhun, E; Bonneville-Levard, A; Meyronnet, D; Garin, G; Pérol, D
Abstract: BACKGROUND: Vismodegib (V) suppresses sonic hedgehog (SHH) signaling. We postulated that vismodegib together with chemotherapy may be more efficient than chemotherapy alone in patients (pts) relapsing of a SHH-activated medulloblastoma (MB). MATERIAL AND METHODS: Adult pts with recurrent SHH-MB not previously exposed to temozolomide (T) were randomly assigned (2:1 ratio) to Arm A (V daily 150mg/d, po) + T (D1-5: 150 mg/m 2 for cycle 1 and 200 mg/m 2 thereafter; n=up to 25pts) or Am B (T alone; n=up to 13pts). Identification of SHH activation was performed centrally by IHC (GAB1, β-catenin, filamin A, and YAP1). NGS analyses were performed to identify the mutations responsible for SHH activation. Primary objectives were to assess the incidence of severe toxicities (safety run-in based on a 3 + 3 design) and the 6-month non-progression rate (NPR-6m) according to WHO criteria and based on central read tumor assessment (Phase II). A Minimax Simon's two-stage design was used to detect NPR-6m of 55% (p0 : 30%, type I error rate of 5%, power of 80%). At first stage, ≥ 3/9 pts without progression at 6m were required for the accrual of 16 additional pts in Arm A. A 3 rd independent and parallel arm with V as single agent (Arm C, n= up to15pts) was added for pts previously treated by T. RESULTS: 24 SHH-MB pts were enrolled (Arm A: 10, Arm B: 5 and Arm C: 9; median age: 37 y [21–55]). At the end of the safety run-in; no major safety concerns were reported. At the end of Stage I: no objective response were reported and 2 pts among 10 were free of progression at 6m among in Arm A. According to statistical rules, the study was definitively closed to enrolment. NGS analyses showed a PTCH1 inactivating mutation in 6 pts (n=4 in arm A; n= 2 in arm B); a SMO activating mutation in 4 pts (n= 3 in Arm A; n=1 in Arm B). For 1 pt in each arm, no tumor sample was available for analysis, for 1 pt in Arm A DNA quality was insufficient, and for 1 patient in each arm no mutations of SMO, PTCH1, SUFU or SHH were found. Out of the 4 pts in Arm A with an inactivating PTCH1 mutation, only 1 was progression free at 6m. PFS and OS data will be presented at the meeting. CONCLUSION: The combination of vismodegib with monthly T failed to demonstrate superior activity as compared with T alone. Further studies are warranted to refine therapeutic indication for vismodegib